Flat Panel CT Scanning Is Helpful in Predicting Hemorrhagic Transformation in Acute Ischemic Stroke Patients Undergoing Endovascular Thrombectomy - Chen, Liuwei (Biomed Res Int, 2021)
PURPOSE: Hyperdense lesions are frequently revealed on flat panel CT (FP-CT) immediately after endovascular thrombectomy in patients with acute ischemic stroke. This study is aimed at discriminating hyperdense lesions caused by extravasation plus hemorrhage from those caused by contrast extravasation alone. METHODS: We retrospectively analyzed clinical and radiological data of patients who underwent an immediate postprocedure FP-CT scan and a follow-up noncontrast CT 24 hours after thrombectomy. We especially focused on the Maximum Hounsfield Units (HU(max)) of each hyperdense lesion. A hyperdense lesion was judged to be hemorrhagic when it persisted on noncontrast CT and/or developed a mass effect. RESULTS: Of 81 patients included in this study, 32 (39.5%) patients presented 41 hyperdense lesions on FP-CT. The chance of hemorrhagic transformation is higher in patients with hyperdense lesions on FP-CT than that in patients without hyperdense lesions (23/32 vs. 1/49, p < 0.001). The HU(max) of hyperdensity on FP-CT can predict hemorrhagic transformation with an area under the curve of 0.805 (95% CI: 0.67-0.94, p = 0.02). The sensitivity, specificity, positive, and negative predictive values of hyperdensity on FP-CT for hemorrhagic transformation were 96%, 84%, 72%, and 98%, respectively. A HU(max) of >600 predicted hemorrhagic transformation with a sensitivity of 50% and a specificity of 100%. CONCLUSIONS: The presence of hyperdensity on FP-CT can predict hemorrhagic transformation with a high sensitivity and negative predictive value. The measurement of HU(max) of hyperdense lesion on FP-CT can be applied to the management of patients undergoing endovascular recanalization.